INTERNALISASI AKHLAK NABAWIYAH MELALUI PROGRAM MADROSATUL QUR’AN DI SMP SUNAN KALIJOGO JABUNG MALANG - Ula, Yusi Aimatul; Firdausia, Nury Firdausia (STAI Ma'had Aly Al-Hikam Malang, 2022)
Excessive use of technology has a negative impact and causes a moral crisis. Educational institutions are a forum for students in handling these cases. SMP Sunan Kalijogo 2 Jabung has a new breakthrough by holding the Madrosatul Qur'an. The purpose of this study is to describe the implementation of the Madrosatul Qur'an program, the supporting and inhibiting factors, the results of internalizing the Nabawiyah through the Madrosatul Qur'an. This research is a mixed methods with explaratory sequential design. The results showed; 1) The Madrosatul Qur'an at SMP Sunan Kalijogo 2 is a Qur'an reading program which is carried out every day before learning, 2) the supporting factors are trained teachers and the pesantren environment. the inhibiting factor is that students are less religious and less time allocated, 3) The results of internalizing Nabawiyah through this program Students have consistent honesty, responsibility, good reasoning, and being open to others